Research progress in clinical characteristics, diagnosis and prognosis of TdT-negative lymphoblastic lymphoma/acute lymphoblastic leukemia - HOU Shumin; SHAO Jingbo (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2023)
Terminal deoxynucleotide transferase (TdT) is a special deoxyribonucleic acid (DNA) polymerase. It can bind a single deoxynucleotide to the 3′-OH end of a DNA molecule in the absence of a template. TdT is a specific intracellular marker of immature lymphocytes in the hematopoietic system, which is of great significance in the diagnosis of lymphoid tumors. The diagnosis of lymphoblastic lymphoma/acute lymphoblastic leukemia (LBL/ALL) depends on immunotyping. TdT is usually positive in LBL/ALL, which is an important basis for clinical diagnosis of LBL/ALL. TdT-negative LBL/ALL is rare in clinical practice. Because of its strong specificity in diagnosis, negative TdT will bring certain difficulties to the diagnosis. There are many reasons for negative TdT. The expression of TdT is different in different differentiation stages of lymphocytes, and the sensitivity of different detection methods and the false negative of TdT can be seen occasionally. In addition, it has been reported that the clinical characteristics and prognosis of TdT-negative- and TdT-positive-LBL/ALL are different. Understanding the significance of TdT expression, the causes of negative TdT, and the different characteristics of TdT-negative- and TdT-positive-LBL/ALL are helpful for clinical diagnosis, treatment selection and prognosis judgment. In this paper, relevant literature at home and abroad is reviewed, and the causes of negative TdT, the clinical characteristics, diagnosis and prognosis of TdT-negative-LBL/ALL were reviewed.